Application of Technology Acceptance Model (TAM) on Computerized Land Activities - Wahyu Prabawati Putri Handayani; Mugi Harsono (Jurnal Economia, 2016)
Abstract: Application of Technology Acceptance Model (TAM) on Computerized Land Activities. The purpose of this study was to examine and analyze the effect of the Technology Acceptance Model (TAM) on computerized land activities. A survey methodology used to collect data of 100 employees. The results indicated that (1) Computer self-efficacy affected the perceived ease of use and usefulness of the technology, (2) the perceived ease of use technology affected of perceived usefulness and attitude towards using technology, (3) the perceived usefulness affected attitude towards using technology, and (4) the attitude to use technology affected intention to use technology.Keywords: Technology Acceptance Model (TAM), computer self-efficacy, perceived usefulness, attitude to use technology, intention to use technologyAbstrak: Aplikasi Technology Acceptance Model (TAM) Pada Komputerisasi Kegiatan Pertanahan. Tujuan penelitian ini adalah untuk menguji dan menganalisis pengaruh Technology Acceptance Model (TAM) Pada Komputerisasi Kegiatan Pertanahan. Sebuah metodologi survey digunakan untuk mengumpulkan data 100 karyawan. Path analysis menunjukkan bahwa (1) Computer self-efficacy berpengaruh pada persepsi kemudahan penggunaan dan persepsi manfaat teknologi, (2) Persepsi kemudahan penggunaan teknologi berpengaruh pada persepsi manfaat dan sikap untuk menggunakan teknologi, (3) Persepsi manfaat teknologi berpengaruh pada sikap dalam menggunakan teknologi, dan (4) Sikap untuk menggunakan teknologi berpengaruh pada niat untuk menggunakan teknologi.Kata kunci: Technology Acceptance Model (TAM), computer self-efficacy, persepsi manfaat teknologi, sikap menggunakan teknologi, niat menggunakan teknologi